Weltanschauung Nūr dalam Al-Qur’an: Analisis Semantik Toshihiko Izutsu dan Refleksi Nilai Pendidikan - Mira Pitriani; Asep Sopian; Hikmah Maulani (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This article examines the concept of nur (light) in the Qur'an through Toshihiko Izutsu's semantic approach and his insights into the values of Islamic education. Employing a qualitative methodology with document analysis, this study investigates the semantic structure of the term nur in the Qur'an and its significance for Islamic educational values. The primary data comprises 38 verses from 24 surahs that contain the term nur, selected based on symbolic and semantic criteria. From this, seven key verses were chosen for detailed analysis. Data were collected through a literature review and analyzed using Izutsu's relational semantic framework, which incorporates syntagmatic and paradigmatic analysis. The findings indicate that nur possesses a lexical meaning as light, along with a relational meaning that reveals its syntagmatic and paradigmatic relationships, which contribute to the theocentric worldview of the Qur'an, encompassing divine guidance, faith, knowledge, and spiritual transformation. The concept of nur serves not only as a metaphysical symbol but also carries practical implications for Islamic education. It embodies values such as the purification of the soul, moral development, the pursuit of knowledge, and submission to God. The symbol of light in the Qur'an suggests that education transcends cognitive aspects, fostering moral and spiritual awareness. This article contributes theoretically by integrating Toshihiko Izutsu's relational semantic approach with the concept of Islamic educational values grounded in revelation, thereby creating new avenues for the development of Islamic curricula and the study of interpretation. Abstrak Artikel ini membahas konsep nūr (cahaya) dalam Al-Qur’an melalui pendekatan semantik Toshihiko Izutsu serta refleksinya terhadap nilai-nilai pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif dengan analisis dokumen untuk mengkaji struktur semantik kata nūr dalam Al-Qur'an dan relevansinya dengan nilai-nilai pendidikan Islam. Data primer terdiri dari 38 ayat dari 24 surah yang mengandung nūr, yang dipilih berdasarkan kriteria simbolik dan semantik. Dari sana, tujuh ayat kunci dipilih secara sengaja untuk analisis mendalam. Data dikumpulkan melalui tinjauan pustaka dan dianalisis menggunakan kerangka kerja semantik relasional Izutsu, yang melibatkan analisis sintagmatik dan paradigmatik. Hasil penelitian menunjukkan bahwa nūr memiliki makna leksikal sebagai cahaya, serta makna relasional yang relasional yang menunjukkan bahwa nūr memiliki relasi sintagmatik dan paradigmatik yang membentuk pandangan dunia Qur’ani yang teosentris seperti petunjuk ilahi, keimanan, ilmu pengetahuan, hingga transformasi spiritual. Konsep nūr tidak hanya sebagai simbol metafisik, tetapi juga memiliki implikasi praktis dalam pendidikan Islam. Ia mencerminkan nilai-nilai seperti penyucian jiwa, pembentukan akhlak, pencarian ilmu, dan ketundukan kepada Tuhan. Simbol cahaya dalam Al-Qur’an menunjukkan bahwa pendidikan tidak hanya bersifat kognitif, tetapi juga membentuk kesadaran moral dan spiritual. Artikel ini memberikan kontribusi teoretis dengan mengintegrasikan pendekatan semantik relasional Toshihiko Izutsu dengan konsep nilai pendidikan Islam berbasis wahyu, yang membuka ruang baru dalam pengembangan kurikulum Islam dan studi tafsir.